Politics of childhood: perspectives from the South - Raman, Vasanthi (2000)
While there is growing concern with issues of children's rights, a Eurocentric perspective has dominated discourses on the subject. This article argues that for a truer perspective to emerge, it is vital to relate the debate to the contemporary Indian reality - the immediate environment, the inherited socio-cultural aspects and issues of gender and caste. - Reproduced
Keywords: Rights of the child - India; Rights of the child